Development and field evaluation of a cardamom polishing machine - ANU RAY MATHEW; Prof. C. P Muhammad (Guide) (Tavanur 1999 Kelappaji College of Agricultural Engineering and Technology)
This study showed that the parameters drumspeed, feed/batch and retention time had significant influence on cleaning efficiency, s[lit percentage and energy consumption. The physical properties of cardamom along with their dependence on moisture content were also studied.
Development and field evaluation of a cardamom polishing machine